Dinámica familiar interna de dos madres adolescentes que viven con su familia de origen en la ciudad de Cali - Millán Castaño, Tatiana (Universidad de San Buenaventura - Cali, 2018)
Adolescent pregnancy is currently seen as a phenomenon worldwide, especially because it is considered a problem that causes negative consequences for society in general. This article intends to think about the internal configurations established within the families of origin of two adolescents from the city of Cali, about how each of the members of these families began to mobilize from the arrival of a new member to their families homes. In-depth interviews are conducted with both adolescents and their family of origin. After the results, it is evident how the internal family dynamics of these adolescents does not undergo radical transformations, but rather the course continues similar to before becoming pregnant. Both families present different subjective findings, developed in the conclusions section. Within the discussion, they develop category by category, integrating the two stories, detailing similarities and differences between both families. Some of the categories worked were conjugal diary of adolescent mothers, specifically in this category similar aspects are evident in the outcome of the affective relationships of adolescent mothers. At the same time, results are found from the exploration of the parental relationship of the triad, results are presented in terms of protective and risk factors to which the adolescent mothers were possibly exposed. This research was carried out from the theoretical perspective of psychoanalysis, which served as a basis for analyzing the results obtained.